The role of corporate culture and its crisis after COVID-19 in healthcare organizations - Sarysheva D.B.; Lipovka A.V. (Алматы Менеджмент Университет, 2023)
The structure of corporate culture went through significant change and crisis during COVID-19. As the base of any organization or corporate, managerial work and culture need constant innovation and update. This article analyses the significance of corporate culture in 204 healthcare and tries to point out how it reaches high productivity and a safe working environment. The paper aims to investigate the current crisis of corporate culture after COVID19 and its growing importance for improving the efficiency of the enterprise. Through conducted interviews and materials used in the research, the work will find out the important points in defining the basic determinants of the corporate culture. New eterminants of the crisis and the ways of overcoming them are to be analyzed.
Keywords: corporate culture; COVID-19; healthcare system; elements of corporate culture